Resilience in child maltreatment: Contributions to understanding the significant factors in the process from an ecological model - Morelato, Gabriela (2011)
The present study aims to integrate resilience concepts within the context of a theoretical model for child maltreatment, the ecological model, as well as to describe risks and protective factors leading to a better interaction as a dynamic process. Thinking deeply about maltreatment from the point of view of resilience implies focusing on the serious consequences it produces, as well as on the assessment of children’s resources to continue growing and developing despite the risks. We may promote children’s potential by understanding resilience within a child maltreatment framework based on this model (interactional, bidirectional and reciprocal).